Influence of Mn incorporation on the structural and optical properties of sol gel derived ZnO film - Caglar, Yasemin; Ilican, Saliha; Caglar, Mujdat; Yakuphanoğlu, Fahrettin (Springer, 2010)
Undoped and manganese doped ZnO (ZnO:Mn) films were prepared by sol gel method using spin coating technique. The effect of Mn incorporation on the structural and optical properties of the ZnO film has been investigated. The crystalline structure and orientation of the films have been investigated by using their X-ray diffraction spectra. The films exhibit a polycrystalline structure. Mn incorporation led to substantial changes in the structural characteristics of the ZnO film. The scanning electron microscopy (SEM) images of the films showed that the surface morphology of the ZnO film was affected by the Mn incorporation. The transparency of the ZnO film decreased with the Mn incorporation. The optical band gap and Urbach energy values of the ZnO and ZnO:Mn films were found to be 3.22, 3.19 eV and 0.10, 0.23 eV, respectively. The optical constants of these films, such as refractive index, extinction coefficient and optical dielectric constants were determined using transmittance and reflectance spectra. The refractive index dispersion curve of the films obeys the single oscillator model with dispersion parameters. The oscillator energy, E (o) , and dispersion energy, E (d), of the films were determined 5.30 and 16.26 eV for ZnO film and 5.80 and 12.14 eV for ZnO:Mn film, respectively.
Keywords: ZnO; Mn doping; Sol gel; Optical constants; Single oscillator model